DEPOSITIONAL AND DIAGENETIC BARRIERS, BAFFLES AND CONDUITS: PERMIAN – CARBONIFEROUS UNAYZAH RESERVOIR, NUAYYIM FIELD, CENTRAL SAUDI ARABIA. (January 2017) - Al‐Ramadan, K.; Franks, S.G.; Al‐Shammari, S.; Rees, A.; Koeshidayatullah, A.; Abu‐Khamsin, S.
Abstract : The Unayzah Formation is one of the most important Palaeozoic reservoir systems in Saudi Arabia. In the Nuayyim field, Central Saudi Arabia, it produces light, sweet crude oil and consists of three main reservoir units, in descending stratigraphic order: Unayzah A, B and C. These reservoir units include a wide range of depositional facies deposited under a variety of climatic conditions, from high‐latitude glacio‐fluvial to more temperate playa/lacustrine, floodplain and braided‐fluvial to hot‐arid aeolian environments. Together with the diagenetic changes superimposed on the various depositional facies, this has produced complex reservoir heterogeneity. The effects of this diagenetic and sedimentologic complexity on reservoir quality and compartmentalization are the subject of this paper. Approximately 816 ft of core and 611 core plug samples were examined from three wells which penetrate, completely or in part, the Unayzah reservoir. We combine petrographic and scanning electron microscope analysis with porosity and permeability data and calculated pore throat dimensions to identify fluid conduits, barriers and baffles to fluid flow. A rock classification scheme is proposed which takes into account whether the pore‐level control on fluid flow is due to depositional or diagenetic processes and the composition of depositional or diagenetic phases within the pores. Distinguishing depositional versus diagenetic controls on fluid flow is important for predicting the three‐dimensional geometry of conduits, barriers and baffles, and a priori knowledge of potential reactions between injected fluids and reservoir rocks is important for designing enhanced oil recovery fluids. In the three wells studied, it appears that the Unayzah reservoir is compartmentalized vertically due to the occurrence of diagenetic and depositional barriers and baffles. There is insufficient data to assess the lateral or areal extent of the barriers, baffles and fluid conduits, but the understanding of pore‐level controls on reservoir quality and the rock classification schemes introduced here will provide a starting point for future studies. These studies should combine well logs, seismic and engineering data with data presented here to assist mapping conduits, barriers and baffles across the field. The proposed classification schemes may also prove to be useful for assessing reservoirs in other fields both within Saudi Arabia and elsewhere.